Management of complicated tumor response to tyrosine‐kinase inhibitors in gastrointestinal stromal tumors. Issue 2 (7th May 2019) - Tirotta, Fabio; Fumagalli, Elena; Colombo, Chiara; Morosi, Carlo; Barisella, Marta; Radaelli, Stefano; Frezza, Anna M.; Casali, Paolo G.; Gronchi, Alessandro; Fiore, Marco
Abstract: Background: The aim was to describe complicated tumor response (CTR) to tyrosine‐kinase inhibitors (TKI) in gastrointestinal stromal tumors (GIST) patients. Methods: From 2001 to 2017, data from patients with metastatic (group A) or locally advanced (group B) GIST who received TKI at our institution were collected. We defined CTR as bleeding, abscess, or perforation as surgical complications of TKI. Patients who had progressive disease were excluded. Clinical characteristics were assessed, and time of occurrence and mortality rate recorded. Results: Among 470 patients, 30 developed CTR (6.4%), 26 in group A (6.8%) and four in group B (4.5%) ( P  = 0.43). Bleeding, abscess, and perforation, respectively, were observed in 17 (56.7%), 8 (26.7%), and 5 (16.7%) patients. A conservative approach was possible in 17 (56.7%) cases; four (13.3%) patients received percutaneous drainage, while nine (30%) underwent emergency surgery. The overall rate of mortality was 13.3%. CTR occurred after 1.6 months (median time) from the imatinib mesylate onset in group B and 14 months in group A. Conclusions: While the risk of CTR in early metastatic patients is virtually nil, patients with locally advanced disease should be monitored carefully. CTR as a consequence of TKI therapy do not prevent patients receiving a potentially curative surgery.